ANDROGEN AND CORTISOL SECRETING ADRENOCORTICAL ONCOCYTOMA WITTH UNCERTAIN MALIGNANT POTENTIAL - C, Pei Lin; L, Shueh Lin (Journal of the ASEAN Federation of Endocrine Societies, 2019)
INTRODUCTION Adrenal oncocytic tumours are a rare variant of adrenocortical tumours and consist of oncocytic cells which are abundant in granular eosinophilic cytoplasm. It is usually found incidentally as most are benign and nonfunctional. We report a case of androgen and cortisol secreting adrenal oncocytic tumour of uncertain malignant potential in a young lady. CASE An 18-year-old lady with prior history of bronchial asthma presented with 4 months history of irregular menstruation and was subsequently amenorrhoeic for a year. She had increased facial hair as well as hair growth over her lower limbs during that period. In addition, she also noticed she had deepening of her voice. On examination she had moonlike facies with acne. There was no abdominal striae and genital examination revealed clitoromegaly. Her laboratory examination showed features consistent with hyperandrogenism with raised testosterone 13.7 nmol/L (0.42-7), dehydroepiandrosterone sulfate 65.7 umol/L (4.7-6.7) and she had non-suppressed serum cortisol level with an overnight dexamethasone suppression test of 204 nmol/L. CT abdomen showed a large left heterogenous isodense adrenal tumour with scattered areas of fluid attenuation measuring 10 x 10 x 8.3cm with smooth margins and no calcification. She underwent an uneventful open left adrenalectomy and biopsy results reported an oncocytic adrenal cortical neoplasm with uncertain malignant potential with low mitotic activity and Ki67 proliferative index of less than 5%. Post-surgery she was started on hydrocortisone replacement which was gradually tapered off and follow-up FDG-PET scan was unremarkable. CONCLUSION Adrenal oncocytic tumours with uncertain malignant potential are a rare entity and its long term behaviour is unknown. Due to its malignant potential, close patient surveillance is required in order to detect recurrence.